Analysis of Public Service Quality at the Class II TPI Atambua Immigration Office - Buti, Graceana Elma Mau; Taek, Petrus Ans Gregorius; Sae, Donatus; Mbiri, Adeodatus Januario Barros; Bulqiyah, Hasanul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the current era of rapidly advancing technology, the quality of public services has become an important issue frequently encountered across various sectors of public facilities. One visible indication is the continued existence of public complaints regarding suboptimal service delivery, often expressed through different technological platforms. This situation has led to the emergence of negative perceptions among the public toward government officials responsible for providing public services. This study aims to analyze and understand the quality of public services at the Immigration Office Class II TPI Atambua. In practice, the officers at the Immigration Office strive to improve service quality by focusing on public interest, integrity, and professionalism. The research employs a qualitative method with a descriptive approach, referring to five dimensions of service quality: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. These five dimensions serve as the basis for evaluating the quality of services provided by the Immigration Office Class II TPI Atambua, with the expectation of achieving high-quality public service delivery. The results of the study indicate that the overall quality of public services in the passport application process at the Immigration Office Class II TPI Atambua is categorized as good. However, several aspects still require improvement, particularly in terms of service timeliness.